Phase transitions and dielectric properties in Bi(Zn1/2Ti 1/2)O3-(Na1-yLiy)NbO3 perovskite solid solutions - Chien Chih Huang (2018)
Perovskite solid solutions based on the system Bi(Zn1/2Ti 1/2)O3-NaNbO3 were obtained via solid-state processing techniques. The crystal structure and ferroelectric phase transitions were studied by means of X-ray diffraction and dielectric measurements. A stable perovskite phase was obtained for Bi(Zn1/2Ti 1/2)O3 substitutions up to 10mol%. The dielectric characterization revealed that as the Bi(Zn1/2Ti1/2)O 3 content increased, the transition temperature decreased and the transition peak became very diffuse. The polarization hysteresis loop and strain measurements presented evidence of an induced ferroelectric phase with 1 mol % Bi(Zn1/2Ti1/2)O3 substitutions. The planar coupling factor (kp) for 0.01Bi(Zn1/2Ti 1/2)O3-0.99NaNbO3 was measured to be 0.28. In addition, with the substitution of Li for Na in the Bi(Zn1/2Ti 1/2)O3-(Na1-yLiy)NbO3 system, the diffuseness of the transition peak decreased and the transition temperature increased. © 2009 The Japan Society of Applied Physics.